Evaluación agronómica de cultivares de sorgo granífero en la EEA Cerro Azul. Campañas 2013/14y 2014/15 - Fariza, Silvina Ines; Heck, Mónica Isabel; De Lucia, Adrían Darío; Blaszchik, Jorge Ariel (EEA Cerro Azul, INTA, 2021)
In the last years Misiones's province has shown a sustained growth in livestock and dairy production. The existence of seasonal forage deficits and the ability of sorghum to consistently perform in harsh environments, place it, as a productive alternative for the region. In order to generate local information about the agronomic performance of cultivars of sorghum available on the market and identify genotypes with better aptitude for grain production for the province, a total of 6 cultivars of sorghum were evaluated in two agricultural cycles in the EEA INTA Cerro Azul (Misiones) through phenological and morphological variables and yield components. Significant differences between cultivars for yield, thousand grain weight, plant height and days to flowering were found. The cultivars had short and intermediate cycles, with an average height of 155,8 cm. The average yield was 5245,4 kg ha-1, highlighting the cultivar GEN 21 T with 6624,07 kg ha-1. While the values of thousand kernel weight ranged between 20,3 g and 32,3 g. The interannual variations observed requires the increase of the number of environments and years of evaluation to identify materials with adaptation to specific niches or wider areas. It is expected to analyze the stability of these materials to make appropriate recommendations for other environments.